Factors associated with the choice of public health service among nursing students in Thailand. Issue 1 (December 2017) - Sawaengdee, Krisada; Pudpong, Nareerut; Wisaijohn, Thunthita; Suphanchaimat, Rapeepong; Putthasri, Weerasak; Lagarde, Mylene; Blaauw, Duane
Abstract Background Despite the fact that public and private nursing schools have contributed significantly to the Thai health system, it is not clear whether and to what extent there was difference in job preferences between types of training institutions. This study aimed to examine attitudes towards rural practice, intention to work in public service after graduation, and factors affecting workplace selection among nursing students in both public and private institutions. Methods A descriptive comparative cross-sectional survey was conducted among 3349 students from 36 nursing schools (26 public and 10 private) during February-March 2012, using a questionnaire to assess the association between training institution characteristics and students' attitudes, job choices, and intention to work in the public sector upon graduation. Comparisons between school types were done using ANOVA, and Bonferroni-adjusted multiple comparisons tests. Principal component analysis (PCA) was used to construct a compositerural attitude index ( 14 questions). Cronbach's alpha was used to examine the internal consistency of the scales, and ANOVA was then used to determine the differences. These relationships were further investigated through multiple regression. Results A higher proportion of public nursing students (86.4% from the Ministry of Public Health and 74.1% from the Ministry of Education) preferred working in the public sector, compared to 32.4% of students from the private sector (p  = <0.001). Rural upbringing and entering a nursing education program by local recruitment were positively associated with rural attitude. Students who were trained in public nursing schools were less motivated by financial incentive regarding workplace choices relative to students trained by private institutions. Conclusions To increase nursing workforce in the public sector, the following policy options should be promoted: 1) recruiting more students with a rural upbringing, 2) nurturing good attitudes towards working in rural areas through appropriate training at schools, 3) providing government scholarships for private students in exchange for compulsory work in rural areas, and 4) providing a non-financial incentive package (e.g. increased social benefits) in addition to financial incentives for subsequent years of work.